Deposit Collecting: Unbundling the Role of Frequency, Salience, and Habit Formation in Generating Savings - de Mel, Suresh; McIntosh, Craig; Woodruff, Christopher (American Economic Review, 2013)
We report on a field experiment using several methods for collecting deposits made in formal bank accounts in rural areas in Sri Lanka. We find that only frequent, face-to-face collection increases aggregate household savings. Collection involving community lock boxes increases balances at the collecting bank, but not overall household savings. Only community box collection appears to have the possibility of being financially viable. The various collection methods allow us to unbundle the role of frequency, salience and habit formation in deposit decisions. We find that frequency and salience affect the number of transactions, but not the level of savings.